Characterization of Orexin Gene in Tilapia (Oreochromis niloticus):Regulator Feeding Appetite, and Correlation with Reproductive Factors - Simanjuntak, Ricky Febrinaldy; Barlian, Anggraini; Wibowo, Indra; ., Rukisah (Jurnal Biodjati, 2024)
The mechanism of energy allocation related to increased appetite and feed intake in fish involves several neuropeptides encoded by specific genes. Orexin (OX) is a peptide secreted in the pars tuberalis of the hypophysis that acts as a stimulator in appetite increase (orexigenic factor). However, the expression of different orexigenic factors varies among vertebrate species, reflecting their unique types and lineages. Therefore, this study aimed to identify genes encoding appetite in Tilapia. RNA isolation, complementary Deoxyribose Nucleic Acid (cDNA) cloning, and DNA amplification were performed from brain samples of gonadally mature Tilapia. The PCR products were subsequently sent to Macrogen.Inc for sequencing. The amplification results of Orexin with β-Actin (positive control) observed using agarose gel electrophoresis showed that the size of the nucleotide base product of each gene was 196 bp and 197 bp. Confirmation of sequencing results carried out using the Basic Local Alignment Search Tool (BLAST) method - National Center for Biotechnology Information (NCBI) for Orexin and β-Actin were 97% and 100%. Based on these results, it can be concluded that each target gene isolated from the tilapia brain showed homology/similarity with the sequence available in the NCBI database